Enhancing Learning Quality and Student Engagement: Utilizing Digital Technology in Islamic Education - Firdaus, Ahmad; Amrullah, Amar; Robiatul Adawiyah, Lelly; Yuliati Zakiah, Qiqi; Supiana, Supiana (International Journal of Nusantara Islam, 2023)
The progression of science and technology has ushered in an era where knowledge, technology, and information have become inextricably intertwined with the realm of education. This prevailing reality underscores the imperative for Islamic universities to proficiently institute pedagogical management strategies. The primary objective of this study is to comprehensively examine and critically analyze the pivotal role of technology-driven digital learning within the domain of Islamic Religious Education (PAI). To achieve this objective, the study employs a qualitative research approach, utilizing the methodology of a thorough literature review. The findings of this research assert that the incorporation of digital technology in the realm of Islamic Religious Education unequivocally augments the overall quality of the educational experience while concurrently enhancing student engagement. It is imperative to recognize that educators, particularly lecturers, wield a pivotal influence in cultivating the requisite proficiencies and knowledge base among students. The innovation encompassed within technology-based digital learning encompasses the stages of discovery, development, and dissemination of digital technology utilization. The components encompassing digital content, curriculum design, faculty training, and the requisite supporting infrastructure collectively constitute indispensable facets in the evolution of digital technology. Inarguably, digital technology serves as an instrumental catalyst in heightening student engagement and optimizing the efficacy of the learning process. However, it is of paramount significance to underscore that the role of lecturers remains pivotal, as they assume the multifaceted functions of facilitators and adept learning managers